Relations among network coding, index coding, and guessing games: the linear case (2012)
Abstract. This paper is a monograph on some relations among Network Coding, Index Coding, and Guessing Games. We have focused on the linear case. We present in detail the most important results. The purpose is that the reader appreciates the profound connexions among these seemingly different areas of Network Theory.